Peningkatan Motivasi Belajar Matematika Siswa Menggunakan Model Teams Games Tournaments Pada SMP Parepare - Nurtasya Fahira Tasya (Prodi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Muhammadiyah Parepare, 2023)
Student involvement in the learning process is still minimal and the lack of student attention seems very boring. So that all these problems affect students' motivation to learn mathematics. This is caused by the teacher still carrying out the learning process which only uses the lecture method and students do not get the opportunity to be active in learning activities. Therefore, this study aims to increase students' motivation to learn mathematics using the Teams Games Tournaments model at SMP Negeri 12 Parepare.This research is a Classroom Action Research (CAR) which consists of two cycles and each cycle consists of 4 stages, namely planning, implementing action, observation, and reflection. The subjects of this research were students of class VIII. C SMP Negeri 12 Parepare with a total of 24 students. The research data was obtained using research instruments in the form of observation sheets to determine the activities of teachers and students in using the TGT model and questionnaires to measure student motivation. The results of the analysis of students' motivation to learn mathematics from cycle I to cycle II experienced an increase. This is evidenced by the average score of students' motivation to learn mathematics in the first cycle of 66.83 in the medium category, while in the second cycle it increased to 87.33 in the high category.So that the TGT learning model can increase the motivation to learn mathematics in class VIII.C SMP Negeri 12 Parepare.